2017
DOI: 10.1590/1807-3107bor-2017.vol31.0051
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of TGF-β1 and MMP-9 in periapical lesions

Abstract: The objective of this study was to evaluate the expression of matrix metalloproteinase 9 (MMP-9) and transforming growth factor beta (TGF-β1) in periapical lesion samples correlated with the intensity of the inflammatory infiltrate and thickness of the epithelial lining. Forty-five cases of periapical lesions (23 periapical granulomas and 22 radicular cysts) were subjected to morphological and immunohistochemical analyses using anti-MMP-9 and anti-TGF-β1 antibodies. The data were analyzed using the following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…It also has been demonstrated that the immunohistochemical investigation became a very important moment in the differential diagnosis and in the staging of this kind of pathology [14]. Immunohistochemical techniques to date can also be used in the diagnostic framework of inflammatory diseases [15,16]. Together with traditional immunohistochemical techniques, alternative methods and specific markers for the classification of the pathology was used more frequently [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…It also has been demonstrated that the immunohistochemical investigation became a very important moment in the differential diagnosis and in the staging of this kind of pathology [14]. Immunohistochemical techniques to date can also be used in the diagnostic framework of inflammatory diseases [15,16]. Together with traditional immunohistochemical techniques, alternative methods and specific markers for the classification of the pathology was used more frequently [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The development and persistence of chronic periapical lesions is a dynamic and complex process whose pathogenesis is intimately linked to the host immune response (Álvares et al 2017;Galler et al 2021), as well as to the type of microorganism involved since the bacterial composition in the infected root canal can influence macrophage polarization (Mantovani et al 2007;Li et al 2013). However, this polarization is only one factor of the immune response in chronic periapical lesions (Weber et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As metaloproteinases da matriz estão envolvidas na lesão periapical de humanos e importância dessas proteases na patogênese da lesão periapical, principalmente para diferenciar cistos e granulomas periapicais de humanos foi demonstrada por meio da avaliação da expressão e atividade de metaloproteinases da matriz utilizando microarrays de DNA, zimografia in situ e imunohistoquímica 13,20 . As metaloproteinases da matriz foram imunomarcadas em tecidos periapicais de humanos previamente e foi proposto que as MMP-1, -8, -9 e -13 estão envolvidas na expansão das lesões periapicais 14,21 .…”
Section: Introductionunclassified
“…Estudos prévios demonstraram que a expressão de MMP-1 em cistos periapicais de humanos está restrita ao tecido epitelial circundando a lesão, macrófagos subepiteliais, fibroblastos e células endoteliais, enquanto durante o desenvolvimento da lesão periapical de ratos, observou-se a expressão de MMP-1 em regiões do tecido ósseo que estão em processo de reabsorção ativa 23,24 . Por outro lado, foi relatado que a expressão de MMP-9 e -13 foi mais intensa na zona de células inflamatórias na lesão, indicando que diferentes metaloproteinases da matriz são produzidas e secretadas em sítios distintos, por células que compõe a lesão periapical 13,20,25 . Estes resultados sugerem que cada metaloproteinase da matriz desempenha um papel específico na patogênese da lesão periapical.…”
Section: Introductionunclassified